Enhanced oil recovery and residues utilization of oil sludge through nitric acid pretreatment process. Issue 3 (June 2019) - ZuoJiao, Kaichao; Zhang, Zheng; Li, Panjie; Jiang, Caiyun; Liu, Jiaxun; Wang, Yuping
Abstract: A cost-effective approach to realize both oil recovery and residues utilization of oil sludge (OS) was proposed. It was an oxidation/acidification-assisted pretreatment process, where nitric acid (HNO3 ) was employed before the procedure of pyrolysis. Effects of dosage and concentration of HNO3 on oil recovery rate from OS were studied. Under the optimal conditions (dosage:5 mL·(g −1 dried OS); concentration: 5 mol·L −1 ), method of this work demonstrated two advantages: higher oil recovery rate of 27.53% and lower residue pyrolysis temperature of 550 °C were obtained, respectively. Detailed mechanism of such results was investigated via characterizations and analyses, among which saturates, aromatics, resins and asphaltenes (SARA) contents and metals contents were associated with the phenomena. Both oxidation and acidification caused the change of component in OS, giving the two conclusions: more saturates produced and less metals contents left. Meantime, the adsorption behavior of pyrolysis residues was evaluated via methylene blue (MB) adsorption tests. The highest MB adsorption value reached to 89.25 mg·g -1 and Langmuir isotherm model was well fitted the equilibrium data. Overall, the oxidation/acidification-assisted pretreatment of OS through HNO3 can be suggested as an economic and effective option.